2020
DOI: 10.5114/jcb.2020.94583
|View full text |Cite
|
Sign up to set email alerts
|

Verification of needle guidance accuracy in pelvic phantom using registered ultrasound and MRI images for intracavitary/interstitial gynecologic brachytherapy

Abstract: Purpose: In combined intracavitary/interstitial (IC/IS) gynecologic brachytherapy, trackers attached to interstitial needles of localize real-time needle trajectories, and intraoperative ultrasound (US) images provide updated anatomy information during needle insertions. To achieve an effective visualization and image guidance, real-time needle trajectories and US images can be unified in preoperative magnetic resonance imaging (MRI) image space together. This study evaluates the rigid registration accuracy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Our research group tested the feasibility of guiding needle placement by registered US images in gynecologic interstitial brachytherapy. While the use of preoperative MRI images had been reported 16 in our previous study, this experiment demonstrated that under ideal conditions, rigid registration between CT images and US images obtained high accuracy for real-time image guidance.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our research group tested the feasibility of guiding needle placement by registered US images in gynecologic interstitial brachytherapy. While the use of preoperative MRI images had been reported 16 in our previous study, this experiment demonstrated that under ideal conditions, rigid registration between CT images and US images obtained high accuracy for real-time image guidance.…”
Section: Discussionmentioning
confidence: 66%
“…In our CT-based brachytherapy, the mean target registration error (TRE) in the phantom was similar to the MRI-based brachytherapy (0.935 ± 0.166 mm vs. 1.01 ±0.22 mm in the axial plane and 0.916 ± 0.143 mm vs. 1.14 ± 0.20 mm in the sagittal plane). In the MRI-based brachytherapy, 16 the mean angle difference ± SD between US images and interstitial needle’s real-time space model was 1.61 ± 0.28 degrees for five needles in the phantom. We will analyze the entire needle trajectory as future work for CT-based brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to address the problem of insufficient stability of a single sensor, Max Q.-H. Meng et al proposed a method to solve the problem of intraoperative occlusion as well as limited field of view of optical tracking systems by fusing multiple monocular optical sensors in an array [24], and Zhang Y. D. et al proposed a method based on the fusion of intraoperative ultrasound images with electromagnetic localization to achieve movement tracking of intraoperative local lesion locations [25]. Jiang-Sun et al oriented to the problem of image navigation during surgery improved the intraoperative navigation rate and alignment accuracy by ultrasound and magnetic resonance image fusion method [26]. All of the above researches have made a lot of useful explorations in intraoperative navigation.…”
Section: Introductionmentioning
confidence: 99%